A comparison of competencies between problem-based learning and non-problem-based learning program nursing graduates. - Applin H (Comparison of Competencies Between Problem-based Learning & Non-problem-based Learning Program Nursing Graduates, 2008)
Nursing-graduate competence is necessary to ensure safe, ethical, and legal practice. Methods such as problem-based learning (PBL) and non--problem-based learning (NPBL) are used in nursing education to bridge the gap between theory and practice and improve graduate competence. The objective of this research was to compare the differences in competence between graduates from a PBL nursing program and those from an NPBL nursing program. This study involved a convenience sample of 121 nursing graduates in Alberta, Canada, who had been practicing for at least six months in a graduate role and whose nursing program utilized a PBL or an NPBL curriculum. The data-collection instruments included self-reports, and the data analysis involved descriptive statistics (mean, mode, and median) and inferential statistical tests (t-tests and ANOVA) to determine the differences in the two groups' mean scores. There was no statistical significance in the mean scores between the two groups, which indicates no difference in entry-to-practice competency preparation after the completion of a four-year nursing program. The teaching method may be perceived as an important variable for change and support for the graduate's competence; however this study indicates no difference between PBL and NPBL course-delivery methods. The significant finding is that all four-year nursing programs in Alberta that use PBL or NPBL support CARNA's entry-to-practice competencies. The graduates were asked how their nursing program prepared them to meet the competencies listed in the questionnaire, and the following themes emerged from the data: PBL---critical thinking, evidence-based practice, competencies as evaluation tools, self-directedness, and teamwork; and NPBL---clinical practice, competencies as evaluation tools, and critical thinking. The graduates were also asked to suggest improvements for nursing programs to better prepare graduates to meet the entry-to-practice competencies. The following themes emerged from the data: PBL---increased clinical time, and combined PBL and NPBL teaching and learning methods; and NPBL---more clinical time and discussion of more real-life scenarios in the classroom.